KARAKTERISTIK IBU HAMIL KURANG ENERGI KRONIS (KEK) DI KECAMATAN TILANGO KABUPATEN GORONTALO - Anna Y. Pomalingo; Denny Indra Setiawan; Misnati Misnati (JOURNAL HEALTH AND NUTRITIONS, 2018)
ABSTRACT Chronic Energy Deficiency at women in childbearing age and pregnant women tend to give birth with low birth weight. Prevalence of Chronic Energy Deficiency at women in childbearing age in Gorontalo Province is 14,3% while in Gorontalo District is 16,9%. Data from Department of Health of Gorontalo District in Sub-district of Tilango show that in 2015, there are 45 Chronic Energy Deficiencies at pregnant women out of 330 pregnant women or 13,6% and it improves to 52 people or 15,7% in 2016. Objective: to obtain description of characteristics of Chronic Energy Deficiency at pregnant women in Sub-district of Tilango, District of Gorontalo in 2017. Significance of Research: The research is expected to be new discourse for people particularly pregnant women on the importance of maintaining health and adequate nutrition in order to avoid Chronic Energy Deficiency problem that may have bad impact to either mothers or fetus. Methodology of Research: it applies quantitative method. It is a survey research with descriptive approach. Analysis: it applies descriptive analysis to describe every variable, either independent or dependent variable. This analysis is distribution of frequency and percentage at every variable. Conclusion: pregnant woman education that has Chronic Energy Deficiency is just elementary school aged 20 to 35 years, mostly work as housewife and have monthly income for less than one million rupiah. Keywords: Pregnant women, Chronic Energy Deficiency ABSTRAK Gizi merupakan salah satu faktor penentu utama kualitas sumber daya manusia. Peran gizi dalam pembangunan kualitas sumber daya manusia telah dibuktikan dari berbagai penelitian. Gangguan gizi pada awal kehidupan akan mempengaruhi kualitas kehidupan berikutnya (Depkes, 2012). Status gizi ibu sebelum dan selama hamil dapat mempengaruhi pertumbuhan janin yang sedang dikandung. Tujuan dari penelitian ini yaitu untuk memperoleh gambaran karakteristik ibu hamil KEK di Kecamatan Tilango Kabupaten Gorontalo Tahun 2017. Manfaat Penelitian ini diharapkan dapat menjadi wacana baru bagi masyarakat terutama para ibu hamil agar mempunyai gambaran tentang pentingnya memelihara kesehatan dan gizi yang memadai pada saat hamil agar terhindar dari masalah KEK yang akan berdampak buruk pada ibu maupun janin. Metodologi penelitian ini menggunakan Metode Kuantitatif dengan pendekatan survey deskriptif. Hasil penelitian menunjukkan bahwa responden yang memiliki tingkat pendidikan tertinggi sejumlah 9 orang (50%), Paritas ibu hamil KEK tertinggi sejumlah 13 orang (72,2%), ANC ibu hamil KEK tertinggi adalah ANC baik sebanyak 12 orang (66,7%), dan Konsumsi tablet Fe ibu hamil KEK tertinggi adalah tidak mengkonsumsi sebanyak 11 orang (61,1%). Kata Kunci: Ibu Hamil, Gizi, Kurang Energi Kronis